Student Perception of the Practical Exam of Introduction to the Clinic in Fourth Semester Medical Students - Yadir López Peña; Zulema Ávila González (Journal of Education Method and Learning Strategy, 2026)
Teaching semiotics in healthy patients is the primary objective of the Introduction to Clinical Practice course. This course is a cornerstone of early medical training, enabling students to acquire the skills and abilities to perform a complete, objective, and organized physical examination—an indispensable competency for future healthcare professionals. The objective of this study is to evaluate the perceptions of fourth-semester medical students regarding the Introduction to Clinical Practice Practical Exam. A descriptive, cross-sectional, and analytical study was conducted in March 2025. Descriptive analyses of frequencies, percentages, means, and standard deviations were performed. Forty-two valid responses were analyzed. Most items received scores above 70% in the "Strongly Agree" category. Overall means were high in the dimensions of Utility and Benefit and Logistics and Organization, indicating a highly positive perception. The Personal Experience dimension received the lowest rating. The practical exam is perceived as an essential component of initial medical training, consistent with previous evidence supporting the use of structured clinical assessments.